Geographical distribution of torture: An epidemiological study of torture reported by asylum applicants examined at the Department of Forensic Medicine, University of Copenhagen - Busch, Johannes Rødbro; Hansen, Steen Holger; Hougen, Hans Petter (Torture Journal, 2018)
Using reports from 154 examinations of alleged torture victims among asylum applicants to Denmark conducted by the Department of Forensic Medicine, University of Copenhagen, between 2001 and 2013, we have categorized the victims into four geographical regions, as well as according to the conflict that caused them to flee. The torture incidents described by the victims were divided into 12 different categories defined by the Istanbul Protocol. These data were cross-referenced in order to identify any differences in the prevalence of the 12 forms of torture. The study showed that crush injuries were only reported by refugees from Asia, including Afghanistan and Pakistan, and that incidents of electrical torture were reported twice as frequently by torture victims from Middle Eastern and North African countries, though it was lower among Iraqis, Iranians and ethnic Kurds. Sexual torture was reported by 78% of females and 25% of males.